The fraud taxonomy in financial reports in the brazilian stock market - Olokodana, Noel Kentinus; Gonçalves , Rodrigo de Souza; Nascimento, Monize Ramos do (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: To explore the types of fraud in financial reports that occur in publicly traded Brazilian companies. Methodology: The Sanctioning Proceedings (Processos Administrativos Sancionadores - PAS) of the Brazilian Securities and Exchange Commission (Comissão de Valores Mobiliário - CVM) were analyzed and a taxonomy of frauds was developed. Results: The following taxonomy is suggested: overestimation of assets, transactions with related parties, diversion of funds to offshore entities, overestimation of loss of asset value (impairment), overestimation of revenue, fictitious revenues, underestimation of expenses. Contributions of the Study: The study brings to the attention of academics, regulators, investors, and companies the types of frauds committed. Knowledge of the taxonomy of frauds draws the attention of regulators to preventatively seek out these types of frauds in the financial reports disclosed. Discussions on the taxonomy of frauds in financial reports bring to the attention of academics and professionals (accountants, auditors and administrators) the forms that distortions of accounting information can take. For auditors (internal or external) and internal control professionals, the taxonomy of frauds in financial reports allows preventive action to avoid or limit the occurrence of these frauds. The lack of the usual types of frauds in the Brazilian market was found. This research seeks to contribute by exploring the types of frauds in financial reports that occur in publicly traded Brazilian companies.